THE EFFECT OF MONEY AVAILABILITY, TIME AVAILABILITY AND PROMOTION OF IMPULSE PURCHASE BEHAVIOR OF CHOCOLATE SNACK PRODUCTS THROUGH POSITIVE EMOTIONS - Pranoto, Hadi; Andarwati, Andarwati; Sunaryo, Sunaryo (Jurnal Aplikasi Manajemen, 2021)
This study examines and analyzes the influence of money available, time availability, and the promotion of impulse purchases through positive emotions as a mediating variable on chocolate snack products. This research is quantitative research conducted in Hypermart Malang Town Square (Matos), Giant Hypermarket Malang Olympic Garden (MOG), Giant Ekstra Sawojajar, and Giant Ekstra Kebonagung. The population studied were consumers who bought chocolate snack products on impulse purchases. The sample used 190 respondents. Data collection techniques using questionnaires, interviews, and literature review. Data analysis techniques in this research use validity test, reliable test, linear test, diagram test, PLS, and hypothesis test on the variable of money availability, time availability, promotion, impulse purchase, and positive emotion on chocolate snack product. This study indicates that the variable availability of money can impact positive emotional variables. The varying availability of money cannot impact impulse buying variables. The time availability variable does not affect the positive emotional variables. Meanwhile, the time availability variable impacts the impulse buying variable. Furthermore, promotional variables affect positive emotional variables as well as impulse buying variables. However, the positive emotional variable has no impact on the impulse buying variable. The positive emotional variable proved the relationship between money and promotional variables' variable availability in the mediation test. In contrast, the variable availability of time is not a provable positive emotional variable as a liaison influence the variable of time availability with impulse buying.